PERILAKU MASYARAKAT KOTA DENPASAR DALAM MENGKONSUMSI MAKANAN CEPAT SAJI (FAST FOOD) - Putu Ari Mulyani; Ni Wayan Ari Sudiartini; Ni Luh Putu Sariani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
This study aims to determine and analyze the factors that influence the behavior of the people of Denpasar in consuming fast food where there is the highest percentage of commodity types of population expenditure, namely in the food and beverage sub-group which has increased from year to year with the most regional classification is urban and experienced a significant increase in 2018 namely 44.12 percent in urban areas and 32.31 percent in rural areas. This shows that people prefer to consume processed foods and beverages rather than make their own home-made foods or consume traditional foods and urban communities tend to spend more on consuming processed foods and beverages. The data used in this study are primary data in this study obtained through the distribution of questionnaires to respondents who have met the established criteria and secondary data in this study were obtained from the Central Statistics Agency. The variables analyzed use path analysis to determine the direct and indirect effects and the Multiple Test to determine the level of significance of the intervening variable as a mediating variable. This research was conducted in Denpasar City with 150 respondents. The results of the analysis show that buying motives have a positive and significant effect on lifestyle, lifestyle has a positive and significant effect on fast food consumption behavior, lifestyle has a positive and significant effect on culture, culture has a positive and significant effect on fast food consumption behavior, Lifestyle is a variable mediation between buying motives for fast food consumption behavior, Culture is a mediating variable between lifestyle for fast food consumption behavior. Based on the analysis that people tend to prefer fast food than traditional food in the cooking process made themselves so consumers need to consider consuming fast food with a companion supplement nutritional value of fiber are better than consuming fast food. The lifestyle of today can not avoid the era such at this time where the development of technology and information is growing rapidly with the flurry that a wide variety of fast food is certainly an option for the consumer. With the knowledge possessed by the people of the city of Denpasar should be more wise in determining the food menu that is consumed for health.